2021
DOI: 10.1016/j.celrep.2021.108781
|View full text |Cite
|
Sign up to set email alerts
|

Functional connections between cell cycle and proteostasis in the regulation of Candida albicans morphogenesis

Abstract: SUMMARY Morphological plasticity is a key virulence trait for many fungal pathogens. For the opportunistic fungal pathogen Candida albicans , transitions among yeast, pseudohyphal, and hyphal forms are critical for virulence, because the morphotypes play distinct roles in the infection process. C. albicans morphogenesis is induced in response to many host-relevant conditions and is regulated by complex signaling pathways and cellular processes. Perturbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 110 publications
(156 reference statements)
1
15
1
Order By: Relevance
“…Specifically, we observed that glycolysis and several heat- shock genes are upregulated during the M phase, oxidative stress genes are upregulated in a distinct subset of cells likely at the early stage of cell cycle, and ribosomal proteins (RP) are upregulated during the S phase (captured by the simple model depicted in Figure 2D ). Many of these associations are well supported by the literature (Chiu et al, 2011; Finkel and Hwang, 2009; Hossain et al, 2021; Senn et al, 2012), and together provide evidence of the efficacy of our sc- assay to detect cell-to-cell heterogeneity even within untreated C. albicans cultures.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, we observed that glycolysis and several heat- shock genes are upregulated during the M phase, oxidative stress genes are upregulated in a distinct subset of cells likely at the early stage of cell cycle, and ribosomal proteins (RP) are upregulated during the S phase (captured by the simple model depicted in Figure 2D ). Many of these associations are well supported by the literature (Chiu et al, 2011; Finkel and Hwang, 2009; Hossain et al, 2021; Senn et al, 2012), and together provide evidence of the efficacy of our sc- assay to detect cell-to-cell heterogeneity even within untreated C. albicans cultures.…”
Section: Discussionsupporting
confidence: 78%
“…The relationships between stress responses, metabolic processes and cell cycle are summarized in Figure 2D. Since several previous reports associated cell cycle phase with the expression of genes involved in stress responses and metabolism (Brauer et al, 2008;Chiu et al, 2011;Hossain et al, 2021;Senn et al, 2012), we further investigate the patterns of co-expression of these processes in individual cells. First, we re-affirmed that cells with higher expression of genes involved in M phase also have high expression of the heat-shock response (Figure 2E).…”
Section: Figure 1 -Figure Supplement 2 (A)mentioning
confidence: 99%
“…However, due to biological factors such as different translation elongation speed, ribosome queuing and the amino acid composition of the nascent peptide chain, as well as technical issues, such as data normalization issues, ribosome densities as measured by ribosome profiling do not necessarily reflect the protein output of the ribosome [ 56 , 61 ]. Further work will be required to confirm whether these effects are due to translation or another mechanism, such as increased protein stability [ 62 , 63 ]. However, the results demonstrate that a post-transcriptional mechanism regulates key transcription factors that are important for hyphal morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…White-opaque switching occurs most frequently at temperatures below 30°C, whereas biofilm formation and GI tract colonization occur at 37°C [ 14 ]. Two key players in the heat shock response, chaperone Hsp90 and transcription factor Hsf1, also govern expression of biofilm- and hypha-related genes [ 33 ]. A simple model is that Hsp90, Hsf1, or their downstream targets interact with Wor3 to alter its activity.…”
Section: Discussionmentioning
confidence: 99%